2016
DOI: 10.1097/pai.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

p40 in Conjunction With CK20 and E-Cadherin Distinguishes Primary Adnexal Neoplasms of the Skin

Abstract: Although basal cell carcinomas (BCC) show typical histomorphologic features, they sometimes remain difficult in distinction from benign adnexal skin tumors of follicular origin like trichoepithelioma (TE) or trichoblastoma (TB). Consequently, an immunohistochemical marker panel separating described entities would be helpful in clinical routine. Thus, we stained 22 skin lesions (BCC, TE, and TB) against β-catenin, CK20, E-cadherin, p40, and p63. The staining pattern was described and quantified using an immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Jakobiec et al (14) applied CK15 expression to investigate the property of the adenoma sebaceum, and Andruszkow et al (15) utilized CK19 expression for differential diagnosis of the basal cell carcinoma and adenoma sebaceum. Furthermore, it is reported that CK expression levels can be used to diagnose clear cell hidroadenoma (16) and primary neuroendocrine carcinoma (17) clinically, suggesting that detection of CKs may be beneficial to diagnosing epithelial tumor of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Jakobiec et al (14) applied CK15 expression to investigate the property of the adenoma sebaceum, and Andruszkow et al (15) utilized CK19 expression for differential diagnosis of the basal cell carcinoma and adenoma sebaceum. Furthermore, it is reported that CK expression levels can be used to diagnose clear cell hidroadenoma (16) and primary neuroendocrine carcinoma (17) clinically, suggesting that detection of CKs may be beneficial to diagnosing epithelial tumor of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…While both BCC and SCC tumors may show overlapping features of squamous differentiation by being positive for p63 and CK5/6, 19 , 20 positivity for both Ber‐Ep4 and BCL‐2 14 , 21 are most consistent with BCC. Strong expression of EMA (epithelial membrane antigen) and lack of staining for BCL‐2 is more indicative of squamous cell carcinoma (SCC).…”
Section: Discussionmentioning
confidence: 99%
“…Ha Lan and colleagues debated the superior quality of p40; while p40 and pan-p63 antibodies gave similar results for AFX and desmoplastic melanoma, pan-p63 showed higher sensitivity in the detection of cSCSCC relative to p40 (81% vs. 56%, respectively) [86]. Notwithstanding this discrepancy, other recent studies have suggested using p40 in the diagnosis of skin cancer [126,127] and as a gold standard for other tumours as non-small cell lung cancer [128]. In line with increased evidence for the usefulness of p40, a monoclonal MMp40 antibody against ΔNp63 (clone BC28) was produced and is currently commercially available for diagnostics (Roche, Cat No.…”
Section: Diagnostic and Prognostic Value Of P63 In Skin Cancermentioning
confidence: 99%